If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -1x) * 2 + -1x * x = 110 Combine like terms: x + -1x = 0 x(0) * 2 + -1x * x = 110 Reorder the terms for easier multiplication: 0 * 2x + -1x * x = 110 Multiply 0 * 2 0x + -1x * x = 110 Anything times zero is zero. 0x + -1x * x = 110 Multiply x * x 0 + -1x2 = 110 Remove the zero: -1x2 = 110 Solving -1x2 = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x2 = -110 Simplifying x2 = -110 Reorder the terms: 110 + x2 = -110 + 110 Combine like terms: -110 + 110 = 0 110 + x2 = 0 The solution to this equation could not be determined.
| (3x+5)(x-1)=0 | | y=2x(3x) | | m+109+26=180 | | 5d-8=-28 | | (2X+85)= | | 4x+11+6x=2+x-9 | | x(9x-7)=(9x+8)(x-3) | | 4x+8x+11y+2w+3x-2y= | | k(k)=y | | 5x=4+-.1y | | 0=56+7x | | 0.16(18x+30)-8x= | | 4x-7w= | | 13s-234=3s-14 | | 10a-2b=-26 | | 2(9+x)=-15(4+x) | | -6=h/18 | | (7x-6)=6-7x | | 5x+17=5x+98 | | X^3-48=4x | | 30+8n=4(2n+7) | | x=2x-73 | | m+1.89=6.519 | | 7(x+4)=3(x+2) | | -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 |